Stability of Mental Toughness, Sleep Disturbances, and Physical Activity in Patients With Multiple Sclerosis (MS)—A Longitudinal and Pilot Study - Sadeghi Bahmani, Dena; Esmaeili, Leila; Shaygannejad, Vahid; Gerber, Markus; Kesselring, Juerg; Lang, Undine E.; Holsboer-Trachsler, Edith; Brand, Serge (Frontiers in Psychiatry, 2018)
Background: Previous research of patients with multiple sclerosis (MS) focused prevalently on fatigue, depression, and cognitive dysfunction during the clinical course. By contrast, research on the longer-term characteristics of physical activity (PA), psychological functioning, and sleep problems is scarce. The aims of the present study were therefore to examine changes in PA, mental toughness (MT) as a proxy of psychological functioning, and sleep disturbances over a 2-year period of time after disease onset. Methods: A total of 18 patients with diagnosed MS (mean age: M = 34.29 years) took part in this longitudinal study. First, 1–4 weeks after the first symptoms, a neurologist diagnosed the MS. Second, they completed a series of questionnaires covering socio-demographic data, PA, MT, and sleep disturbances. Third, the same questionnaires were completed again 2 years later (follow-up). Last, a neurologist assessed the degree of disability with the Expanded Disability Status Scale (EDSS). Results: Two years after MS onset, patients had lower levels of vigorous PA, but no statistically significant changes in moderate PA were observed. Further, walking time increased and sedentary time decreased. Patients with sleep disturbances at disease onset also reported poor sleep 2 years later. MT scores remained stable over time. EDSS scores worsened, though, change in EDSS was not associated with PA, MT, or sleep. Conclusions: Two years after disease onset, patients with MS reported similar MT levels and sleep disturbances. PA shifted from vigorous PA toward walking and a less sedentary lifestyle, while moderate PA remained unchanged. The pattern of results of the present pilot study suggests that at the early stage of the MS course, there is no obstacle for being physically active, nor did sleep and MT as a proxy of psychological functioning decrease in a substantial way.